An extra-articular procedure improves the clinical outcome in anterior cruciate ligament reconstruction with hamstrings in female athletes - Vadalà, Antonio Pasquale (Springer-Verlag, 2012)
PURPOSE: A positive glide is a common finding after ACL reconstructions, especially in women. The aim of this study was to prospectively evaluate the role of Cocker-Arnold’s extra-articular procedure in reducing the incidence of a residual postoperative rotational knee laxity. METHODS: Sixty patients affected by an ACL injury with a +2 (clunk) or +3 (gross shift) pivot-shift test entered this prospective study; they were randomly assigned to group A (control group, hamstrings) or group B (study group, hamstrings plus Cocker-Arnold). Thirty-two patients entered group A and 28 group B. At follow-up, patients underwent clinical evaluation, KT-1000 arthrometer and Lysholm, Tegner, VAS and subjective and objective IKDC form. RESULTS: At a mean follow-up of 44.6 months, the same expert surgeon reviewed 55 patients (28 group A and 27 group B). The comparison of the results of the evaluation scales used and of the KT-1000 arthrometer did not show statistically significant differences (p > 0.05). Lachman test was negative (S/S) in all the patients of both groups (100 %). A residual positive pivot-shift (glide) was found in 16 patients (57.1 %) of group A and in five patients (18.6 %) of group B (p < 0.05). CONCLUSIONS: The extra-articular MacIntosh procedure modified by Cocker-Arnold in combination with ACL reconstruction significantly reduces the rotational instability of the knee.